Pre-Exposure Prophylaxis with Hydroxychloroquine Does Not Prevent COVID-19 nor Virus Related Venous Thromboembolism - Alessandro Perrella; Valentina Orlando; Ugo Trama; Francesca F. Bernardi; Enrica Menditto; Enrico Coscioni (Viruses, 2021)
Different and several public health strategies have been planned to reduce transmission of pandemic due to SARS-CoV-2 since it started. None drugs have been confirmed as able to prevent viral transmission. Hydroxychloroquine with its immunomodulatory properties has been proposed as potential anti-viral drug in particular for prevention once viral exposure has been happen or in first phases of infection. Furthermore, in several immunological systemic disease hydroxychloroquine was able to reduce the number of thrombotic complications. So, because COVID-19 was associated to immunological imbalance and to thrombotic complications, we retrospectively analyzed the rate of infection in those patients being under treatment with this drug during COVID-19 epidemic outbreak from 8 March until 28 April in particular comparing those with pre-exposure to this treatment and those that were not taking this medication before SARS-CoV-2 viral infections.